PEMBELAJARAN TEKS EKSPLANASI BERDASARKAN KURIKULUM 2013 SISWA KELAS VIII SMP NEGERI 8 SURAKARTA - Pramesti, Dyah Ayu; Wardani, Nugraheni Eko; Ulya, Chafit (Universitas Sebelas Maret, 2020)
The purpose of this study was to describe explanatory text learning based on the 2013 curriculum for class VIII students of SMP Negeri 8 Surakarta. This research uses descriptive qualitative research methods. The results showed that the teacher had carried out three stages in learning, namely planning, implementing, and assessing learning. In the lesson plan, it is stated in the lesson plan (RPP) that is used by the teacher by following the RPP curriculum 2013 format. In implementing the learning process, it was found that some of the teacher's activities had fulfilled the concept of learning in the 2013 curriculum, namely apperception activities, core activities, and closing activities. In the assessment of learning to compile explanatory text, it appears that the teacher only assesses aspects of knowledge, namely students are given the task of compiling explanatory text individually.